Comparable Worth: An Economic and Ethical Analysis - Pincus, Laura (Journal of business ethics, 1998)
This article examines the legal, economic, and ethical arguments supporting and opposing comparable worth. The co- authors advance opposing views on the wisdom of adopting comparable worth as a public policy, and those views are not reconciled within the limits of this essay.